An Analysis of Students’ Mastery on Constructing Simple Present Tense of English Education Department at STAIN Bengkalis - Wan Julia Mayasari (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2021)
This research aimed to determine the students’ mastery on constructing simple present tense of the English Education Department at STAIN Bengkalis and which part would be the easiest and the most difficult to master. The subjects of this study were 19 first-semester students who were given a multiple-choice test. This research was descriptive quantitative and the data were analyzed using SPSS Statistics 20. The findings showed that the student's mastery of constructing simple present tense was at an average level with a mean of 64.08. The easiest part for them to master is affirmative sentences with subjects I, You, We, and They with a mean of 66.32. Meanwhile, the most difficult part was in a negative sentence with a mean of 63.16. The analyses explained that the majority of the students made mistakes in putting ending –s/-es for the verbs with subjects She, He, and It, and also still had problems in forming negative sentences in using auxiliaries do/does. It is recommended to English lecturers have more focuses on giving information in forming a Simple Present Tense.